جريمة المحاباة في الصفقات العمومية - خالدي, خديجة (جامعة الوادي University of Eloued, 2019)
الملخص: تعد الصفقات العمومية الاداة الاستراتيجية التي وضعها المشرع في ايادي السلطة العامة لإنجاز العمليات المالية المتعلقة بتسيير المرافق العامة ، و الوسيلة الامثل لاستغلال و تسيير الاموال العامة ، الامر الذي جعلها مجالا حيويا لتفشي جرائم الفساد بمختلف صورها. ورغبة من المشرع الجزائري في صيانة الأموال العامة، وحمايتها من التبديد وتضيق الخناق على المفسدين عمد من خلال قانون الوقاية من الفساد ومكافحته الى حصر كل الافعال الاجرامية التي تمس بقطاع الصفقات العمومية وبيان اركان قيامها، والعقوبات التي تطبق على من يثبت ارتكابهم لها . ومن خلال هذه الدراسة سنحاول تسليط الضوء على احد اهم و ابراز هذه الأفعال الاجرامية واكثرها انتشارا ألا وهي جريمة المحاباة في الصفقات العمومية. Abstract: The public transactions are a strategic tool that is used by any project to help general authority to achieve financial operation concerning management of public infrastructures. The system of public transaction is the best means to exploit and implement the use of public financing . As the field of transactions constitutes in general an important area where financing move,it is therefore a field of corruption. The project is aiming at protecting the latter and keeps it away from loss, then it is a field of paramount importance within the framework of the strategy of fighting corruption in the field of public transaction. Through the present study ; we are trying to shed some light on one of the most important crime in public transaction ; it is the crime of nepotism in public transaction.
Keywords: المحاباة ; الصفقات العمومية ; الفساد